Giro, Tour and Vuelta in the same season - Lucia, A.; Hoyos, J.; Santalla, A.; Earnest, C. P.; Chicharro, J. L. (British Journal of Sports Medicine, 2003)
The exercise volume and intensity are reported of a male professional cyclist (age 30; VO(2)max 75.0 ml/kg/min) who successfully completed the 2001 Giro d'Italia (May), Tour de France (July), and Vuelta a Espana (September). The total exercise time during the Giro, Tour, and Vuelta was 90 hours 44 minutes (5444 minutes), 88 hours 23 minutes (5303 minutes), and 72 hours 59 minutes (4379 minutes) respectively. Heart rate telemetry during the races allowed the exercise intensity to be classified into three phases: I, below the first ventilatory threshold (VT1); II, between VT1 and the second ventilatory threshold (VT2); III, above VT2. Compared with the Giro and Tour, the lower exercise volume of the Vuelta (about 20% less total time) was compensated for by a considerably lower and higher contribution of phases I and III respectively. As a result, the total load (volume x intensity) in the three races was comparable.